MO833PSYCHOLOGICAL REPERCUSSIONS OF THE LOCKDOWN AND THE COVID-19 EPIDEMIC IN HEMODIALYSIS PATIENTS AND CAREGIVERS IN FRANCE. (29th May 2021) - Prezelin-Reydit, Mathilde; Guerraoui, Abdallah; Dolley-Hitze, Thibault; Vendrely, Benoît; Chantrel, François; Kolko-Labadens, Anne; Azzouz, Lynda; Bouillier, Marc; Pelletier, Solenne; Fessi, Hafedh; Vigneau, Cécile; Combe, Christian; et al.
Abstract: Background and Aims: The health crisis linked to the COVID-19 epidemic has required lockdown measures in France and changes in practices in dialysis centers. The objective was to assess the depressive and anxiety symptoms during lockdown in hemodialysis patients and their caregivers, to assess their coping strategies during this period and to assess the symptoms of depression, anxiety and post traumatic stress beyond confinement. Method: We sent, during lockdown period, between April and May 2020, self-questionnaires to voluntary subjects (patients and caregivers), treated by hemodialysis or who worked in hemodialysis in one of the 14 participating centers in France. We analyzed their perception of dialysis sessions (beneficial or worrying), their stress level (VAS rated from 0 to 10), their anxiety and depressive symptoms (HADS). Factors associated with stress, anxiety and depression were analyzed with multiple logistic regression models. We will look for associations between coping strategies, participant characteristics and symptoms of stress, anxiety and depression using chi-square tests. A second questionnaire was sent out in October to collect symptoms of depression, anxiety and post-traumatic stress beyond confinement. Symptoms will be described and factors associated with stress, anxiety and depression will be analyzed with multiple logistic regression models. Results: 669 patients and 325 caregivers agreed to participate. 70% of participants found it beneficial to come to dialysis during confinement. The proportions of subjects with a stress level ≥ 6 linked to the epidemic, confinement, fear of contracting COVID-19 and fear of infecting a loved one were respectively 23.9%, 26.2%, 33.4% and 42%. 39.2% presented with certain (13.7%) or doubtful (19.2%) anxious symptoms. 21.2% presented a certain (7.9%) or doubtful (13.3%) depressive symptomatology. Age, gender, history of psychological disorders and perception of dialysis sessions were associated with levels of stress, anxiety and depression. 685 subjects participated in the second part of the study (68.9% of the participants of the first part). Analyzes of this data are in progress. Conclusion: During the lockdown period, in France, the majority of hemodialysis patients and caregivers found it beneficial to come to dialysis. One in 3 subjects had anxiety symptoms and one in 5 subjects had depressive symptoms. It will be interesting to investigate if there was an association between the coping strategies implemented by the participants and their level of stress, anxiety and depression during confinement and to analyze the evolution of the anxiety-depressive symptoms over time.